The Effect of Hibiscus Leaf’s Adhesives on the Quality of Cow Dung Husk Charcoal Briquettes - Iwan Ridwan Yusup; Astuti Kusumorini; Siti Risalti Maulida (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
The research to find out the good briquette adhesive has been done, however the results have not been satisfactory yet. This study aims to determine the effect of hibiscus leaf adhesive (Hibiscus rosa-sinensis L) on charcoal briquette organic charcoal. The materials used in the manufacture of cow dung husk charcoal briquettes are rice husk and cow dung. The research was conducted in biology garden of Science and Technology Faculty, Islamic State University of Sunan Gunung Djati Bandung from May to June 2015. The research was conducted by using Random Design Complete (RAL) Factorial 3 X 4 with twice repetition (duplo). There are 3 compositions of treatment rice husk: cow dung, that are: 1: 1, 3: 1 and 1: 3, and addition of 4 levels adhesive from hibiscus leaf (Hibiscus rosa-sinensis L.), that are; control (without adhesive), 10 grams, 15 grams and 20 grams. The results showed that the adhesive combination of hibiscus leaves and the composition of organic charcoal briquettes was highest at density of 0.89 g / cm3, calorific value of 2432.62 cal / g, carbon content of 25.49% and lowest at water content of 8.75 %, vapor content 32.89%, ash content 45%. The best treatment combinations were found in the ratio of rice husk: cow dung ie 1: 3 and adhesive concentration 15 grams with the best heat value of 2431,62 kal /g.